From the Southern Cross : A View of World Art c. 1940-88 : 1988 Australian Biennale. - Waterlow, Nick; Lindsay, Frances; Thomas, Daniel; Art Gallery of New South Wales, Sydney; National Gallery of Victoria, Melbourne; 7th Biennale of Sydney, 1988 (Sydney : Biennale of Sydney, 1988)
Anger, Renate ; Arthur, Tom, Artschwager, Richard ; Asdrubau, Gianni ; Bacon, Francis ; Balson, Ralph ; Balthus ; Beckmann, Max ; Biberstein, Michael ; Bleckner, Ross ; Boltanski, Christian ; Bonnard, Pierre ; Booth, Peter ; Bourget, Marie ; Boyd, Arthur ; Braque, Georges ; Brown-Rrap, Julie ; Brus, Günter ; Buthe, Michael ; Cadieux, Geneviève ; Charlesworth, Sarah ; Collins, Hannah ; Combas, Robert ; Dawson, Neil ; etc.
From the Southern Cross : A View of World Art c. 1940-88, Presented by The Seventh Biennale of Sydney in association with The Australian Bicentennial Authority, Art Gallery of New South Wales and Pier 2/3, Walsh Bay, Sydney, 18 May - 3 July 1988 ; National Gallery of Victoria, Melbourne, 4 August - 18 September 1988
English
kunstcatalogus